2017
DOI: 10.35188/unu-wider/2017/332-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-household bargaining in poor countries

Abstract: This paper is intended to bridge the theoretical literature describing efficient intrahousehold behaviour and the development literature that collects empirical regularities pointing toward the existence of strategic decision-making among spouses. It examines the key elements of the collective model and discusses its relevance to analysing intra-household behaviour in poor countries. It explores the role that risk and uncertainty, information asymmetries, power imbalances, arranged marriages, strategic investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…Evidence about the relation between information asymmetry, cooperation, efficiency and resource allocation in households in developing contexts includes Ashraf (2009), who showed that one fifth of participants in a lab-in-the-field experiment were willing to give up money to keep returns hidden from their spouse, thereby creating household efficiency losses. In some cases, productive labour efforts, that are not easily observable and subject to information asymmetry, are provided at suboptimal levels and lead to efficiency losses in agricultural households (Baland & Ziparo, 2018). In Ghanaian households, public transfers increased expenditures on household goods, while private transfers were mainly used for private or concealable expenditures (Castilla & Walker, 2013).…”
Section: Research Objectives and Hypothesesmentioning
confidence: 99%
“…Evidence about the relation between information asymmetry, cooperation, efficiency and resource allocation in households in developing contexts includes Ashraf (2009), who showed that one fifth of participants in a lab-in-the-field experiment were willing to give up money to keep returns hidden from their spouse, thereby creating household efficiency losses. In some cases, productive labour efforts, that are not easily observable and subject to information asymmetry, are provided at suboptimal levels and lead to efficiency losses in agricultural households (Baland & Ziparo, 2018). In Ghanaian households, public transfers increased expenditures on household goods, while private transfers were mainly used for private or concealable expenditures (Castilla & Walker, 2013).…”
Section: Research Objectives and Hypothesesmentioning
confidence: 99%
“…The only exceptions we know of are two recent papers, using Bangladeshi data and concentrating on food consumption (Bargain et al 2018, Brown et al 2019). The complex structure and budgetary organization of West-African households with separate spheres of spending suggest that the Pareto optimality assumption supporting those structural models is unlikely to be verified (see Baland and Ziparo 2018). Hence, this route might not be particularly promising in such context.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is relatively substantial empirical support in economics for collective models of intra-household decision-making, models that provide a useful framework for an analysis of gender relations and their implications for resource allocations within couples and households (Baland and Ziparo 2018;Ambler et al 2021). In these models, socalled distributional factors direct the allocation of resources (Doss 2013;Bourguignon et al 2009;Himmelweit et al 2013;Browning et al 2014).…”
Section: Introductionmentioning
confidence: 99%